2018
DOI: 10.1111/fcp.12367
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid produces antidepressant‐like effects in a chronic unpredictable stress model of depression via attenuation of neuroinflammation, oxido‐nitrosative stress, and endoplasmic reticulum stress

Abstract: Depression is a common psychiatric disorder with heavy economic and social burdens. Searching new agents with better antidepressant-like activities is of great significance for depression therapy. Tauroursodeoxycholic acid (TUDCA), a clinical drug for gallstone treatment, possesses neuroprotective effects in different brain disorders. However, whether it affects depression remains unclear. We addressed this issue by evaluating the effect of TUDCA on depression induced by chronic unpredictable stress (CUS). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 52 publications
2
16
0
1
Order By: Relevance
“…Recently, UDCA and TUDCA were demonstrated to enhance the adaptive capacity of the ER and suppresses the ER stress in primary biliary cholangitis . An interesting related study revealed that TUDCA improved the induced depression‐like behaviors likely through attenuation of neuroinflammation and oxido‐nitrosative and ER stress . In addition, the anticataractogenic potential of the bile acids UDCA and TUDCA has been demonstrated and was ascribed to their ability to maintain antioxidant status, to suppress lens epithelial cell death through alleviating the ER stress, and to prevent protein aggregation through enhancement of α‐crystallin chaperone activity .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, UDCA and TUDCA were demonstrated to enhance the adaptive capacity of the ER and suppresses the ER stress in primary biliary cholangitis . An interesting related study revealed that TUDCA improved the induced depression‐like behaviors likely through attenuation of neuroinflammation and oxido‐nitrosative and ER stress . In addition, the anticataractogenic potential of the bile acids UDCA and TUDCA has been demonstrated and was ascribed to their ability to maintain antioxidant status, to suppress lens epithelial cell death through alleviating the ER stress, and to prevent protein aggregation through enhancement of α‐crystallin chaperone activity .…”
Section: Discussionmentioning
confidence: 99%
“…The reduction effect of TUDCA on immobility time in the TST and FST is similar to that of fluoxetine, and is not associated with the change in endogenous spontaneous locomotor activity, suggesting that the TUDCA indeed has antidepressant-like activities in LPS models. The antidepressant-like activity of TDUCA was evidenced further by an observation that the TUDCA treatment prevented LPS-induced decrease in sucrose preference in the SPT, and was supported by one of our recently published studies, in which the TUDCA was found to improve chronic unpredictable stress-induced depression-like behaviors via attenuating neuroinflammation, oxido-nitrosative, and ER stress [20]. To date, the pathophysiological mechanism that mediates the onset of depression remains largely unknown, which to some extent hinders the development of new antidepressants.…”
Section: Discussionmentioning
confidence: 56%
“…On the basis of these contexts, the significance of the present study should be strengthened particularly.Besides the classical monoamine dysfunction hypothesis, the neuroinflammatory hypothesis has been raised to explain the pathogenesis of depression in the past decades. This hypothesis appears to be a new focus for depression study in recent years because the actively involvement of neuroinflammation in depression onset and/or progression has been supported by more and more studies[14,15,19,48,51,52]. For example, the overaccumulation of pro-inflammatory cytokines in the blood and/or brain have been observed repeatedly in depressed patients and animals[14,15,19], and stimulation of animals with proinflammatory cytokines, such as IL-1β and TNF-α, can induce typical depression-like behaviors[51,52].Researchers have observed that peoples who accept a low dose of endotoxin immune (24 h) develop sickness and depressive behaviors [48].…”
mentioning
confidence: 94%
“…For example, some pre-clinical compounds which possess antiinflammatory properties have been confirmed to be capable of ameliorating depression-like behavior in rodents induced by acute immune stress or the other chronic stresses, such as the chronic unpredictable stress and the chronic social defeat stress [16][17][18][19], and some clinical anti-inflammatory drugs, such as nonsteroidal anti-inflammatory drugs (NSAIDs) and minocycline, can suppress depressive symptoms in patients [20,21]. Further, the traditional antidepressants, including the paroxetine, fluoxetine, and imipramine, have been reported to reduce pro-inflammatory responses in the brain in rodents [22][23][24].…”
Section: Introductionmentioning
confidence: 99%